Revenue and taxation: Income tax - LIU, Hern Kuan (Institutional Knowledge at Singapore Management University, 2020)
Written specifically for the legal profession in Singapore by a panel of distinguished local practitioners and academics, Halsbury’s Laws of Singapore provides a succinct narrative statement of core areas of law and practice. Halsbury’s is designed to be the first point of reference for the legal practitioner. This updated chapter on Income Tax includes commentary on the latest statutory amendments, Singapore cases and foreign cases.